Miracles, Convulsions, and Ecclesiastical Politics in Early Eighteenth-Century Paris - Kreiser, B. Robert, 1943- (Book collections on Project MUSE., 1978)
In the midst of the fierce controversies raging in France over the papal bull Unigenitus, worshipers at the tomb of a revered Jansenist deacon in Paris's Saint-Medard cemetery witnessed a variety of miraculous occurrences. These well-publicized events led to the emergence of a cult that came to affect and be affected by the most furious religious debate of the eighteenth-century. Professor Kreiser provides a full and objective account of the conflicts surrounding this unsanctioned cult, which remained a major cause celebre in ecclesiastical politics for nearly a decade.The author details the intricate relationships between Church and State and broadens our awareness of the political implications of popular religion during the ancien regime. His wide-ranging book is the first account of the Saint-Medard episode to deal with this affair in its multiple contexts. At stake was more than acceptance of the papal bull, whose political history the author discusses. Also involved, as he shows, were fundamental questions about the nature of miracles, conflicts between episcopal and priestly authority, the unwelcome intrusions of the papacy in the affairs of the Gallican Church, and struggles among the crown, the Parlement of Paris, and the French episcopate for control over ecclesiastical affairs.Originally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.